2004
DOI: 10.4028/www.scientific.net/kem.257-258.201
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Surface Quality during Ultra-Precision Grinding of Brittle Materials in Ductile Mode

Abstract: The factors influencing surface quality for brittle materials is theoretically analyzed during ultra-precision grinding. Grinding experiments of brittle materials are carried out. The results show that the average abrasive grain size of the diamond wheel has a main influence on the surface quality, and the influence of the wheel speed and feed rate is secondary. In the case of s =1200m/min, f=0-20 µm/rev, and a p =0.1-10µm, only when the average abrasive grain size of the diamond wheel is less than 10µm, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The investigation showed that median and radial cracks did not appear and hence were not the cause of fracture as usually thought. Chen et al [15] investigated and analyzed theoretically, the factors influencing the surface quality of brittle materials, during ultra-precision grinding. Grinding experiments were also carried out to confirm the outcome of theoretical analysis, for the brittle materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The investigation showed that median and radial cracks did not appear and hence were not the cause of fracture as usually thought. Chen et al [15] investigated and analyzed theoretically, the factors influencing the surface quality of brittle materials, during ultra-precision grinding. Grinding experiments were also carried out to confirm the outcome of theoretical analysis, for the brittle materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the present investigation, with four factors, all at five levels (as shown in Table 2) the total number of experiments required was 5 4 , i.e. 625.…”
Section: Methodsmentioning
confidence: 92%
“…Liao and Chen [3] used back-propagation neural networks to model and optimize the creep-feed grinding of alumina with diamond wheels. Chen et al [4] investigated and analysed the factors that influence the surface quality of brittle materials during ultra-precision grinding. Their results showed that the abrasive grain size of the diamond wheel has a significant influence on the surface quality with the wheel speed and feed rate only being of secondary importance.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers, such as Bifano T.G. Namba Y. etc, had made a lot of theoretical analysis and experimental researches [3][4][5], but these materials are hard and brittle mostly. About the removal mode of KDP material, it hasn't researched.…”
Section: Introductionmentioning
confidence: 99%